Embedding Consistent RPL Data Collection Processes in Irish Higher Education Institutions (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
The purpose of this paper is to document how the development, agreement, and implementation of a shared definition of RPL among Irish institutions can address the historical absence of robust and consistent data on RPL beneficiaries – the learners themselves. The paper begins by contextualizing the work within the RPL landscape in Irish higher education, along with providing some background information on the project itself, including how it provided a forum for institutions to come together to engage in dialogue and develop solutions. Using a case study, the paper highlights the importance of aligning technical infrastructure with business process development in achieving successful outcomes for RPL activities. The essay then describes actions taken to develop and implement this common definition across partners institutions. It concludes with a synopsis of the impact of the work and its contribution to the long-term commitment to strengthening RPL implementation and opportunities for learners.